Engineering concerns of flood, 1998 perspective - Ali, M. Ashraf 1965-; Seraj, Salek M.; Ahmad, Sohrabuddin; Bangladesh University of Engineering and Technology (Dhaka : Bangladesh University of Engineering and Technology, 2002)
Contributed articles with reference to Bangladesh.
Includes bibliographical references.
Keywords: Floods -- Bangladesh -- Dhaka; Floods -- Environmental aspects -- Bangladesh -- Dhaka; Groundwater -- Quality -- Bangladesh -- Dhaka; Sanitation -- Health aspects -- Bangladesh -- Dhaka